2019
DOI: 10.3390/molecules24152723
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Flavone Derivatives via N-Amination and Evaluation of Their Anticancer Activities

Abstract: Seventeen new flavone derivatives substituted at the 4′-OH position were designed, synthesized and evaluated for their anticancer and antibacterial activities. Among them, compounds 3, 4, 6f, 6e, 6b, 6c and 6k demonstrated the most potent antiproliferative activities against a human erythroleukemia cell line (HEL) and a prostate cancer cell line (PC3). The results also showed that the IC50 value of compounds 3, 4, 6f, 6e, 6b, 6c and 6k were close to that of the anticancer drug cisplatin (DDP) and lower than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…Thus, we speculated that both of the core nucleus and the groups on the core nucleus might be responsible for the antibacterial activity of STK-35/66, including the -NO 2 , -OOH and N-cyclopropyl groups. Similarly, these active groups have been previously reported as effective antibacterial active group (Zitko et al 2018;Zhang et al 2019b;Asiri et al 2021). In the present study, STK-35 and STK-66 showed the most effective antimicrobial activity against type strains and MDR clinical isolates of Gram-negative pathogens (A. baumannii, E. coli, K. pneumoniae and P. aeruginosa), with minimal inhibitory concentrations (MICs) ranging from 0Á0625 to 8 μg ml −1 and minimal bactericidal concentrations (MBCs) from 0Á125 to 16 μg ml −1 (Table 1 and Table S1).…”
Section: Resultsmentioning
confidence: 60%
“…Thus, we speculated that both of the core nucleus and the groups on the core nucleus might be responsible for the antibacterial activity of STK-35/66, including the -NO 2 , -OOH and N-cyclopropyl groups. Similarly, these active groups have been previously reported as effective antibacterial active group (Zitko et al 2018;Zhang et al 2019b;Asiri et al 2021). In the present study, STK-35 and STK-66 showed the most effective antimicrobial activity against type strains and MDR clinical isolates of Gram-negative pathogens (A. baumannii, E. coli, K. pneumoniae and P. aeruginosa), with minimal inhibitory concentrations (MICs) ranging from 0Á0625 to 8 μg ml −1 and minimal bactericidal concentrations (MBCs) from 0Á125 to 16 μg ml −1 (Table 1 and Table S1).…”
Section: Resultsmentioning
confidence: 60%
“…At present, the cyclization of o -hydroxychalcones using iodine in dimethyl sulfoxide still represents the principal method for the synthesis of flavones and their analogs with various structures. This method is still finding multiple applications because it generally allows for obtaining the target compounds with high yields, while the o -hydroxychalcones needed as precursors can be easily obtained via Claisen–Schmidt condensation [ 30 , 34 , 35 , 46 , 47 , 61 ].…”
Section: Chemical Synthesis Of Flavonesmentioning
confidence: 99%
“…A wide range of 2-aryl-4H-chromen-4-ones, commonly known as flavones, was synthesized via cyclodehydrogenation reaction of (E)-2 0 -hydroxychalcones in the presence of a catalytic amount of molecular iodine in DMSO. The reaction proceeds in a short period of time (15 min to 8 h) and temperatures ranging from 100 °C, 61,62 110 °C, 63,64 120 °C, 65 130 °C, 66,67 140 °C, 68-70 160 °C, 71,72 °C73 to reflux conditions. [74][75][76][77][78][79][80][81][82][83][84][85] The mechanism involves addition of iodine to the CαdCβ double bond; elimination of HI to form the α-iodinated chalcone; cyclization to chroman-4-one via attack of the hydroxyl group to the C-β position and finally elimination of a second HI to afford the desired 4H-chromen-4-one.…”
Section: Synthesis Of 23-unsubstituted 4h-chromen-4-onesmentioning
confidence: 99%